Sharia Economic Transformation in the Era of Industrial Revolution 4.0 - Muhammad Irfan Syah; Koni Piranda; Muhammad Rizky Anes; Zulfikar Hasan (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
.  Industrial Revolution 4.0, marked by technological advances such as artificial intelligence (AI), Internet of Things (IoT), big data, and blockchain, has brought significant changes in various economic sectors, including the sharia economy. Sharia economics, which is based on Islamic principles such as justice, transparency and social responsibility, faces great challenges and opportunities in this digital era. The integration of technology in the sharia economy is important to ensure its relevance and sustainability. This research analyzes the impact of the Industrial Revolution 4.0 on the sharia economy, identifies the necessary transformations, and provides strategic recommendations to overcome existing challenges. The method used is qualitative with document analysis from various primary and secondary sources. The discussion includes the adoption of technology such as blockchain to increase transparency, the use of AI and big data for risk analysis, as well as the development of sharia digital financial products and services. The research results show that technology can increase operational efficiency and sharia financial inclusion, but challenges such as rigid regulations and a lack of technological literacy must be addressed. This research provides in-depth insight into the synergy between technology and sharia principles, and paves the way for sustainable and inclusive innovation in the sharia economy.